Ocena użyteczności języka ojczystego (polskiego) w uczeniu się gramatyki języków obcych (angielskiego i rosyjskiego): wyniki badań - Wach, Aleksandra; Jakowlewa-Pawlik, Marina (Studia Rossica Posnaniensia, 2016)
This article reports a study which gathered Polish learners’ opinions about the usefulness of L1-based techniques in learning L2 English and L3 Russian grammar. The results reveal a negative correlation between the length of study and the level  of positive evaluations of the usefulness of L1-based clues. Although L1 was generally considered more useful in learning Russian, the evaluations differed considerably in relation to particular structures in both languages.